Genética e esclerose lateral amiotrófica : estudo de microRNas e do gene da ATXN2 = Genetics and amyotrophic lateral sclerosis: study of microRNAs and ATXN2 gene - Andrade, Helen Maia Tavares de, 1979- (2018)
Orientadores: Marcondes Cavalcante França Junior, Danyella Barbosa Dogini